Literature and Stylistics for Language Learners
XXIII, 217 p.
Keywords: This volume presents the state of the art in terms of stylistic research and application, including EFL and ESL language classroom situations. Some of the most prominent scholars from a variety of backgrounds in the field of pedagogical stylistics show how theory, empirical studies and new technology, including corpus analysis, can be integrated into the classroom.